124k views
1 vote
Solve for x.
-2(-3x-2)-5x+3=-2

User Xcesco
by
5.6k points

2 Answers

1 vote

Answer: I believe it is -9

Step-by-step explanation: You have to distribute the negative two (-2) with the numbers in parentheses, which will give you 6x+4-5x+3=-2. Then, you combine like terms. 6-5 is one, and 4+3 is seven. You get x+7=-2. You then subtract the 7 from the -2, which gives you -9. Therefore, x= -9

User Martin Studer
by
4.7k points
5 votes

Answer: x=-9

Step-by-step explanation:

> -2(-3x-2)-5x+3=-2

> 6x+4-5x+3=-2 (Distribute -2 to -3x and -2)

> x+7=-2 (combine like terms)

>x=-9 (subtract 7 from both sides)

User Hodl
by
5.7k points